THE MODERATING ROLE OF THE INNOVATION ON THE RELATIONSHIP BETWEEN ACHIEVEMENT, ENABLERS, AND ORGANIZATIONAL EXCELLENCE: ORGANIZATIONAL AND BUSINESS EXCELLENCE MODEL - Mohsen Alamiri; Ali Ameen; Osama Isaac; Ibrahim Alrajawy; Ahmed Hamoud Al-Shibami , (International Journal of Management and Human Science (IJMHS), 2020)
Innovation is not just the process of translating an idea or invention into a good or service that creates value or pays customers. It is an idea that must be replicable at an economical cost and must meet specific needs. Excellence is one of the fundamentals that all international organizations seek to adopt in all fields of work. This will result in increasing the productivity of the Organization and the efficiency of its outputs. The research problem focused on the lack of studies exploring the moderate role of innovation in the relationship between achievement and enabling organizational excellence. The main objectives of this paper were to highlight the need to measure the impact of achievement, empowerment, and innovation in achieving organizational excellence. To achieve these goals, a comprehensive literature review was conducted using descriptive analysis of all academic literature, governmental and non-governmental reports, best practices, and international standards. The conclusions of this paper were reached to show the impact of achievement, empowerment and innovation in achieving organizational excellence.